Antidepressant-like activity of hydroalcoholic extract of Agaricus blazei in stressed and unstressed mice - Haq, Israr ul; Aslam, Muhammad; Ahmed, Hammad; Sultana, Nuzhat (Bangladesh Journal of Pharmacology, 2019)
The aim of this study was to investigate the antidepressant activity of hydroalcoholic extract Agaricus blazei (273 and 819 mg/kg; orally) in stressed and unstressed Swiss albino mice. Mice were immobilized to induce stress. Fluoxetine 20 mg/kg orally was given to stressed and unstressed animals and immobility time was noted by using forced swim test and tail suspension test. The concentration of plasma nitrite was also evaluated in stressed and unstressed mice. The effect of prazosin (α1-adrenoceptor antagonist), p-CPA (parachlorophenylalanine–tryptophan hydroxylase inhibitor) and 7-nitro-indazole (nNOS inhibitor) on the antidepressant activity of A. blazei was also evaluated. A. blazei and fluoxetine significantly decreased the duration of immobility time in stressed and unstressed mice, showing significant antidepressant activity. No substantial change was found in the locomotor activity. However, a significant reduction in the level of plasma nitrite was also noted in stressed mice. Hydroalcoholic extract showed prominent antidepressant activity in mice. Video Clip of Methodology: Forced swim test, Tail suspension test and Open field test: 4 min 17 sec: Click to watch